EFFECT OF CONCENTRATION OF IMPERATA CYLINDRICA L LEAF EXTRACT ON SYNTHESIS PROCESS OF GOLD NANOPARTICLES - Iwan Syahjoko Saputra; Yoki Yulizar; Sudirman Sudirman (Jurnal Sains Materi Indonesia, 2018)
Gold Nanoparticles (GoldNPs) successful was performed using HAuCl4 precursor as Au3+ ion source with 7x10-4 M concentration. The research aims to knows effect of concentration variation of Imperata cylindrica L leaf extract on synthesis process of gold nanoparticles. The research used of green synthesis method. Colloid of nanoparticles which is formed in analyzed using UV-Vis Spectrophotometer, FT-IR Spectroscopy, PSA, PZC, XRD and TEM. The results of synthesis showed the best concentration of Imperata cilindrica L leaf extract at 3,46%, happen a shift of wavelength at UV-Vis from 216 nm to 530 nm with 1.779 absorbance value. The PSA analysis showed a particle size of 51.87 nm and a PZC value of -19.2 mV. The result of FT-IR indicated a shift of wavenumber in the hidroxyl group from 3354 cm-1 to 3390 cm-1 and showed a interaction of hydroxyl group at imperata cylindrica L leaf extract with Au3+ ion. TEM analysis shows the morphology of GoldNPs that spherical shape with a particle size of 20 nm. XRD calculation results show crystallite size of gold nanoparticles is 15.47 nm.